Assistive Technologies: Saviour of Mathematics in Higher Education - Reddy, Pritika; Reddy, Emmenual; Chand, Vishal; Paea, Sione; Prasad, Avinesh (Frontiers in Applied Mathematics and Statistics, 2021)
The pervasion and inclusion of new technologies into teaching and learning processes are continuously changing the higher education landscape. Selected and specific technologies termed as "Assistive Technologies" are being used as key tools for enabling students to access education, actively and independently participate in the education process, improving learning and supporting inclusive education. This paper presents students’ preception of the use of various assistive technologies such as mobile learning, tablet learning, lecture capture, gamification and online intelligent systems that have been developed for learning and student support at a higher education institute. There is also a broad discussion on how these can be adopted and adapted in higher education mathematics. It is well documented that students have low-esteem towards or while doing the subject and have math phobia, particularly in higher education. An online questionnaire on the students' perception of using assistive technologies was deployed to the mathematics students. The results show that assistive technologies are indeed a saviour of mathematics with a significantly positive attitude garnered towards using them for learning mathematics.